Methodology ISO 9001: 2015 in the footwear industry (GEON Journal (Management, Organizations and Business), 2017)
This research is part of the document that integrates a proposal of organizational efficiency with the theme of quality management systems in the footwear industry of Guanajuato. Shoe companies are not benefiting from internationally accepted quality models and used to ensure the quality of their processes and products. As part of updating the contents of the research, we investigated the methodology that will help organizations move from the 2008 version to the latest version in 2015 of the ISO 9001 model, with the aim of providing the procedures to be formulated through a clear and simple process to continue with the certification of the design and manufacturing processes of footwear companies in the region.The steps followed in the research are described graphically in a process where the footwear industry in the State of Guanajuato was established as a contextual or referential theoretical framework, as well as the problematization of it in reference to quality, making the documentary analysis of nine cases of studies carried out from 2012 to 2015 by specialized institutions in the shoe industry.
Keywords: Footwear industry; Quality management system; ISO 9001: 2015